Alcohol and other drugs: prevalence, demographic characteristics and perceived effects on the academic performance of high school students within the Mogalakwena Municipality of Limpopo Province. - Owo, Owo Ikwa (My University, 2013)
INTRODUCTION: Smoking, alcohol and other drugs use among high school learners has become a major public health problem across the globe. Here in South Africa, it is estimated that a large proportion of learners indulge in smoking and the use of alcohol and illicit drugs. Data from treatment sites across the country indicate that the number of patients who are below 20 years seeking treatment is escalating. These indulgences have been blamed for escalating school violence, rapes, robbery and accidents, all of which contribute to increased morbidity, disability and premature deaths. It is expected that the result of this study may provide additional understanding about learners’ drug and alcohol use. Such additional understanding can be of benefit to those responsible for the planning and implementation of cessation programmes. AIM AND OBJECTIVES: To determine the extent of drug and alcohol use, the relationship between substance use and academic performance, and the factors that may influence cessation of alcohol and drug use among high school learners in Mogalakwena municipality. METHOD: The protocol involved purposeful selection of one school from each of the nine education circuits within the Mogalakwena Municipality, Limpopo Province. The questionnaire was anonymous, requiring no data that can identify any learners. The sample consisted of five hundred and fifty five students aged 15 to 23(53% females and 47% males). The data was coded and analysed with epi-info version 6(Dutch) and this involved descriptive statistics and cross tabulations with specific reference to chi square test and students t-test yielding p-values. RESULTS: The result of this study indicate that among high school learners in the Mogalakwena municipality 28% have smoked cigarette, 65% have drunk alcohol and 16% have used illicit drugs.In addition there was statistically significant difference between urban and rural learners in terms of smoking and alcohol consumption, with higher rates among urban students, but there was no difference in the use of drugs between the two groups. Also, there was statistically significant difference in drug usage and smoking with regard to age but no difference in alcohol consumption. Younger students tended to smoke more and also were more involved in the use of drugs. More males than females were involved in smoking, alcohol consumption and drugs use. The most reported factors that could influence cessation of alcohol and drugs use were bad effect 49%, cost 23% and parents’ influence 15%. Among the parameters examined as proxies for impact of alcohol and other drugs use on academic performance, indications point to negative impact. CONCLUSION: Alcohol and other drugs use is prevalent among high school learners in the Mogalakwena municipality and is reported to have a negative impact on academic performance. “Bad effects”, high costs and significant relationships are reported as the most important factors that could influence alcohol and other drugs use cessation and these may be important considerations in planning risk reduction.
Keywords: Alcohol Drinking--adverse effects; Drugs--adverse effects